Antigenic modulation of the cytophilic binding of guinea-pig IgG and IgM antibodies to homologous macrophages. - Webster, R O (1979)
The cytophilic binding of immune complexes by peritoneal exudate cells (PEC) from adjuvant-stimulated guinea-pigs was studied using 125I-labelled guinea-pig IgG1, IgG2 and IgM antibodies to the dinitrophenyl (DNP) group. The influence of hapten density upon cytophilic activity was studied by the addition of DNP-conjugated antigens to antibody in 2-200 molar ratios of DNP:antibody. Only IgG2 binding was enhanced by immune complex formation, and the increased binding of IgG2 anti-DNP was dependent on the number of DNP determinants per antigen molecule. Cytophilic activity with epsilon-DNP-L-lysine (DNP-LYS), alpha,epsilon-di-DNP-L-lysine (DNP-LYS-DNP), or DNP1-8-BSA was no greater than that seen in the absence of hapten. Increased cytophilic binding was noted only with DNP20-41-BSA. The binding of IgG2 and IgG2 anti-DNP:DNP-bovine serum albumin (BSA) complexes was inhibited by monomeric IgG2. The relative cytophilic capacities of guinea-pig immunoglobulins appeared as follows: IgG greater than IgG1 greater than IgM. IgG1 and IgM binding of DNP conjugates did not enhance their cytophilic activity; therefore, IgG1 and IgM cytophilic binding to PEC was considered biologically insignificant. This investigation provides further evidence that cytophilic binding of immune complexes to macrophages is due to the co-operative action of multiple Fc sites rather than a conformational change in the IgG2 antibodies, and serum proteins, notably complement components, can alter the binding and/or phagocytosis of IgG2 anti-DNP:DNP-BSA complexes.